Plankton : a guide to their ecology and monitoring for water quality - Suthers, I. M. (Iain MacLeod), 1958-; Rissik, David (Environmental scientist) (CSIRO Publishing, 2009)
Plankton is an invaluable reference for environment managers, water authority ecologists, estuary and catchment management committees, coastal engineers, and students of invertebrate biology, environmental impact assessment and marine biology. This practical book provides a comprehensive introduction to the biology and ecology of plankton and describes its use as a tool for monitoring water quality. All the major freshwater and coastal phytoplankton and zooplankton groups are covered and their associated environmental issues are discussed. A chapter on best practice in sampling and monitoring explains how to design, implement and conduct meaningful phytoplankton and zooplankton monitoring programs in marine and freshwater habitats, as well as how to analyse and interpret the results for effective management decision-making. Real-life case studies demonstrate the use of plankton for identifying and monitoring water quality issues.